Answer:
A
Explanation:
We have the system of equations:
-3x + 4y = -22
2x + 7y = 5
Let's solve this using elimination, so multiply the first equation by 2 and the second equation by 3:
2 * (-3x + 4y = -22) ⇒ -6x + 8y = -44
3 * (2x + 7y = 5) ⇒ 6x + 21y = 15
Our equations are now:
-6x + 8y = -44
6x + 21y = 15
Add these two together to eliminate the x term:
-6x + 8y = -44
+ 6x + 21y = 15
______________
0x + 29y = -29
y = -29/29 = -1
Plug this back into one of the equations to find x:
-3x + 4y = -22
-3x + 4 * (-1) = -22
-3x - 4 = -22
-3x = -18
x = -18/(-3) = 6
The answer is (6, -1) or A.